Attention to Attention - Ocasio, William (Organization Science, 2011)
Organizational theory and research has increased attention to the determinants and consequences of attention in organizations. Attention is not, however, a unitary concept but is used differently in various metatheories: the behavioral theory of the firm, managerial cognition, issue selling, attention-based view, and ecology. At the level of the brain, neuroscientists have identified three varieties of attention: selective attention, executive attention, and vigilance. Attention is shaped by both top-down (i.e., schema-driven) and bottom-up (i.e., stimulus-driven) processes. Inspired by neuroscience research, I classify and compare three varieties of attention studied in organization science: attentional perspective (top-down), attentional engagement (combining top-down and bottom-up executive attention and vigilance), and attentional selection (the outcome of attentional processes). Based on research findings, I develop five propositions on how the varieties of attention in organization provide a theoretical alternative to theories of structural determinism or strategic choice, with a particular focus on the role of attention in explaining organizational adaptation and change.